2009
DOI: 10.2105/ajph.2007.131631
|View full text |Cite
|
Sign up to set email alerts
|

Public Awareness and Use of Direct-to-Consumer Genetic Tests: Results From 3 State Population-Based Surveys, 2006

Abstract: We conducted population-based surveys on direct-to-consumer nutrigenomic testing in Michigan, Oregon, and Utah as part of the 2006 Behavioral Risk Factor Surveillance System. Awareness of the tests was highest in Oregon (24.4%) and lowest in Michigan (7.6%). Predictors of awareness were more education, higher income, and increasing age, except among those 65 years or older. Less than 1% had used a health-related direct-to-consumer genetic test. Public health systems should increase consumer and provider educat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
39
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 14 publications
4
39
1
Order By: Relevance
“…Less than 1% of our study sample reported having had a DTC genetic test, which is very similar to findings from national surveys (Goddard et al, 2006;Kolor et al, 2009). However, over half of these participants gave discordant answers to questions assessing DTC use.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Less than 1% of our study sample reported having had a DTC genetic test, which is very similar to findings from national surveys (Goddard et al, 2006;Kolor et al, 2009). However, over half of these participants gave discordant answers to questions assessing DTC use.…”
Section: Discussionsupporting
confidence: 81%
“…Awareness of DTC genetic testing was higher among this highly educated sample of individuals with cancer, their relatives, controls, and self-referrals compared to awareness in national studies (49% vs. 14% or 22%) (Goddard et al, 2006;Kolor et al, 2009). Whether they had a history of cancer or not, those who self-referred into the NWCGN study were more aware of DTC testing than were other participant types.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…These results are similar to a three-state survey of nutrigenomic DTC testing in 2006 that found 14% of people were aware of companies and 0.6% had purchased tests. 6 In an Oregon-only sample for the Centers for Disease Control and Prevention's Behavioral Risk Factor Policy issues in genetics and genomics | ALMELING and GADARIAN…”
Section: Dtc Genetic Testingmentioning
confidence: 99%
“…3 However, many studies are limited by samples that are unrepresentative of the general population, making it difficult to assess the generalizability of the results. [4][5][6] When national polls are conducted, the focus is usually limited to a single condition, such as cancer or depression. 7,8 Additionally, more attention has been given to how individuals respond to genetic risk [9][10][11] rather than assessing their policy opinions.…”
mentioning
confidence: 99%